Functional ultrasound and brain connectivity reveal central nervous system compromise in Trembler-J mice model of Charcot-Marie-Tooth disease - Maximiliano Anzibar Fialho; Mariana Martínez Barreiro; Lucia Vázquez Alberdi; Juan Pablo Damián; Maria Vittoria Di Tomaso; Jérôme Baranger; Mickael Tanter; Miguel Calero; Carlos Negreira; Nicolás Rubido; Alejandra Kun; Javier Brum (Scientific Reports)
Abstract The Charcot-Marie-Tooth-1E (CMT1E) disease is typically described as a peripheral neuropathy in humans, causing decreased nerve conduction, spastic paralysis, and tremor. The Trembler-J (TrJ) mice serve as a high fidelity model of this disease. Here, we use functional ultrasound (fUS) and functional connectivity (FC) to analyze TrJ mice’s brain activity during sensory stimulation and resting state experiments against wild type (WT) mice - the healthy counterpart. fUS is an imaging technique that measures cerebral blood volume (CBV) temporal changes. We study these changes in the primary somatosensory cortex barrel field (S1BF) of both mice populations during periodic vibrissae stimulation, measuring the number of pixels that correlate to the stimulation (i.e., the size of the activation area), the average correlation of these pixels (i.e., the response strength), and the CBV’s rate of change for each stimulation (i.e., the hemodynamic response). Then, we construct a FC matrix for each genotype and experiment by correlating the CBV signals from the eight cortical regions defined by the Paxinos and Franklin atlas. Our results show that TrJ mice have significantly diminished neurovascular responses and altered brain connectivity with respect to WT mice, pointing to central nervous system effects that could shift our understanding of the CMT1E disease.